Women in Top Management and Bank Performance: Evidence from Indonesia - Sawitri, Hunik Sri Runing; Untoro, Wisnu; Trinugroho, Irwan (UI Scholars Hub, 2016)
We investigate the impact of the presence of women in top management on bank performance controlling for bank specific factors, ownership and governance. By making use of sample of 70 Indonesian banks in a cross section study, we find strong evidence that the presence of women in the executives is negatively associated with firm performance. Moreover, we examine the moderating effect of TMT organizational tenure and TMT age. However, only little evidence is found in the effect of our moderating variables.